Stanning and Stalling: The Mediating Effect of Fear of Missing out in the Association Between Celebrity Worship to Academic Procrastination - Ali, Moondore Madalina; Dhowi, Bay; Suharyanto, Carolus; Angelina, Vania; Budiman, Nikodemus (Bulletin of Counseling and Psychotherapy, 2025)
Many Indonesian teenagers identify themselves as avid fans of Korean pop (K-Pop) idols, displaying remarkable loyalty and dedication to their idols. This deep devotion often manifests as celebrity worship, characterized by a parasocial bond between fans and their beloved celebrities. This intense parasocial relationship can pose distractions and detrimentally impact academic performance, potentially fostering academic procrastination. Moreover, this phenomenon is compounded by the pervasive fear of missing out (FOMO), further amplifying distractions and negative effects on academic activities. This research aimed to explore the associations between celebrity worship and academic procrastination, with a particular focus on the potential mediating role of FOMO. Employing a predictive correlational design, the research delves into the experiences of 534 Indonesian teenagers entrenched involvement in the K-pop fandom. The analysis revealed a significant correlation between celebrity worship and academic procrastination, further nuanced by FOMO's partial mediation. The results indicate how celebrity worship affects academic performance and highlight the need for intervention to reduce the impact of celebrity worship on academic performance.